Structural validity of the Arabic version of the disabilities of the Arm, Shoulder and Hand (DASH) using Rasch measurement model - Ali H. Alnahdi (SpringerOpen, 2021)
Abstract Background The disabilities of the arm, shoulder and hand (DASH) is a commonly used region-specific patient-reported outcome measure (PROM) that quantify upper extremity function (activity limitation) and symptoms. Current evidence suggests that measurement properties of the adapted versions of the DASH are not sufficiently examined. The Arabic DASH has evidence supporting its internal consistency, test-retest reliability, construct validity and responsiveness. On the other hand, the validity of the assumed unidimensionality of the Arabic DASH has not been examined previously. The aim of this study was to examine the structural validity of the Arabic DASH in patients with upper extremity musculoskeletal disorders using Rasch measurement model. Methods Patients with upper extremity musculoskeletal disorders were recruited and were asked to complete the Arabic DASH at their initial visit to physical therapy departments. The overall fit of the Arabic DASH to the requirement of the Rasch measurement model was examined using chi-square statistics for item-trait interaction, mean item and person fit residuals. The fit of individual items, thresholds ordering, local dependency, differential item functioning (DIF), and unidimensionality using the t-test approach were also examined. Results The Arabic DASH did not fit the Rasch measurement model initially (χ2 = 179.04, p < 0.001) with major breach of local item independence and a pattern of high residual correlations among the activity-related items and among the impairment-related items. Combining items into activity-limitation and impairment testlets accommodated the local dependency and led to satisfactory fit of the Arabic DASH to the requirement of the Rasch measurement model (χ2 = 3.99, p = 0.41). Conclusions Rasch measurement model supports the structural validity of the Arabic DASH as a unidimensional measure after the accommodation of local dependency.